A Financial Conditions Index for Norway - Nikka Husom Vonen (Norges Bank, 2011)
Financial conditions indexes (FCIs) may be useful tools for policymakers because they may have the ability to summarize overall financial conditions for households and companies and at the same time provide timely information on real economic activity. A monthly FCI for Norway is constructed by using principal components based on 13 financial variables. Real-financial linkages are examined by correlation analyses and by analyzing in- and out-of-sample fit of a regression model. Through this exercise the FCI is found to be a useful leading indicator of Norwegian GDP growth. Alternative FCIs are also considered, in particular an FCI based on variables purged of business cycle effects.
hdl:11250/2507329
Keywords: 330